Adsorption of malachite green in aqueous solution using sugarcane bagasse-barium carbonate composite - Fan, Xuejing; Deng, Ligao; Li, Kai; Lu, Haiqin; Wang, Ruifeng; Li, Wen (Colloid and interface science communications, 2021)
The use of sugarcane bagasse (SCB) in water treatment has received an increasing amount of attention because of its characteristics and low cost. Bagasse was used as the matrix in this study. Barium chloride and sodium carbonate were mixed with bagasse under certain conditions to generate barium carbonate and to prepare the bagasse‑barium carbonate (SCB-BaCO3) composite adsorbent to adsorb the malachite green (MG) dye in the solution. MG’s adsorption on the adsorbent conformed to the Langmuir isotherm model, and the theoretical maximum adsorption capacity was 1250 mg/g. SCB-BaCO3 composite material is a low-cost, environmentally friendly, and efficient green adsorbent. [Display omitted] •A new type of bagasse‑barium carbonate composite adsorbent was prepared.•The composite adsorbent was used to adsorb malachite green in wastewater.•The adsorption mechanism involved electrostatic attraction.•The preparation process of the adsorbent was green and pollution-free.